Laplacian energy of trees with at most 10 vertices - Masood Ur Rehman; Muhammad Ajmal; Tayyab Kamran (Indonesian Combinatorial Society (InaCombS), 2018)
Let Tn be the set of all trees with n ≤ 10 vertices. We show that the Laplacian energy of any tree Tn is strictly between the Laplacian energy of the path Pn and the star Sn, the authors partially proving that the conjecture hold for any tree Tn, where n ≤ 10.